2020
DOI: 10.3390/agronomy10060853
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Methods and Gypsum Application on Yield and Water Productivity of Wheat under Salinity Conditions in North Nile Delta

Abstract: Salinity and water shortage are the most important factors limiting crop productivity, so increasing the productivity of salt-affected soils is important to address the global food gap. Two field experiments were conducted under typical farm conditions in the North Nile Delta to study the effect of planting methods and gypsum application on wheat yield and water productivity under a range of water and soil salinity levels. In the first experiment, wheat was treated with gypsum (25%, 75%, and 100% gypsum-requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
6
11
0
Order By: Relevance
“…Regarding the study aim of evaluating the water relations for wheat planting dates and planting methods, the study concludes that, among planting methods, bed planting methods saved amounts of irrigation water by 29.5% (1046.07 m 3 •ha −1 , average irrigation applied water in both seasons) in comparison with flat planting method and consumed less water other than planting methods. ese findings are in agreement with the results obtained by Aboelsoud et al [58] who illustrated that the highest Aw values were obtained with the traditional flat planting method and the lowest Aw values were achieved with wheat planted with raised furrows, by Li et al [53] who identified the advantage of bed technique from higher savings of irrigation water with less local machinery and labor costs, and by Fahong et al [59] who showed that using furrow irrigation rather than flood irrigation could reduce irrigation by up to 30% and enhance water use efficiency.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the study aim of evaluating the water relations for wheat planting dates and planting methods, the study concludes that, among planting methods, bed planting methods saved amounts of irrigation water by 29.5% (1046.07 m 3 •ha −1 , average irrigation applied water in both seasons) in comparison with flat planting method and consumed less water other than planting methods. ese findings are in agreement with the results obtained by Aboelsoud et al [58] who illustrated that the highest Aw values were obtained with the traditional flat planting method and the lowest Aw values were achieved with wheat planted with raised furrows, by Li et al [53] who identified the advantage of bed technique from higher savings of irrigation water with less local machinery and labor costs, and by Fahong et al [59] who showed that using furrow irrigation rather than flood irrigation could reduce irrigation by up to 30% and enhance water use efficiency.…”
Section: Discussionsupporting
confidence: 93%
“…The raised bed (RB) planting method has the potential to improve irrigation water distribution, reduce water use, and increase crop yield and water productivity compared to traditional planting methods [19,20]. Li., et al [21] found that using the RB method increased wheat productivity and solar radiation use efficiency, and they interpreted this as a consequence of the vertical distribution of photosynthetically-active radiation.…”
Section: Introductionmentioning
confidence: 99%
“…These results are also in line with study of Maleha et al (2020) that 29.5% water was saved when wheat was planted on raised beds than broadcast and drill planting techniques. Aboelsoud et al (2020) also reported that more water is required to irrigated flat sown field than ridge/raised bed sown field. Similarly, it was also reported that WUE of furrow irrigation technique is 30% higher than flood irrigation (Fahong et al, 2004).…”
Section: Resultsmentioning
confidence: 99%